Relative Thermoluminescence Response of TLD-100, TLD-200 and GE-doped Optical Fiber to 8.05 keV X-ray - Mohammed Al - Ruqeish, Y. M. Amin’, M. S.; Chew, S. H.; Wong, C. S. (Malaysian Journal of Science, 2008)
The responses of three types of thermoluminescence dosimeters (TLDs), namely the TLD-100, TLD-200 and Ge-doped optical fiber to soft X-ray with photon energy of 8.05 keV were measured. The X-ray source used is the vacuum spark plasma which is capable of producing intense coper Ka line radiation at energy of 8.05 keV. The output dosage of the vacuum spark X-ray source is measured by a calibrated ion chamber and it is found to increase with operating voltage. The TL sensitivities of TLD-100, TLD-200 and Ge-doped optical fiber are determined and results are normalized to their responses to 6Â°Co gamma rays. The TL sensitivities are found to be 1.2 for TLD-100, 29.0 for TLD-200 and 13.8 for Ge-doped Optical Fiber.